2014
DOI: 10.1089/ars.2013.5761
|View full text |Cite
|
Sign up to set email alerts
|

Novel Faces of Heme Oxygenase-1: Mechanisms and Therapeutic Potentials

Abstract: Not only double, Janus face, but numerous appearances characterize heme oxygenase-1 (HO-1), an inducible enzyme which main role is to degrade heme. Recently, the noncanonical functions of HO-1 have particularly attracted researchers' attention. Indeed, understanding the enzyme-independent activities of HO-1 can provide additional chances for translational application of research on HO-1. In this Forum, eight reviews and two original articles describe a plethora of mechanisms in which this pleiotropic protein i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…HO-1 effect is complex due to the multiple products of its activity, the non-canonical actions of the protein and the plethora of interactions of the products and protein with other pathways [141]. [90] and Ahmad et al [64].…”
Section: Remaining Questionsmentioning
confidence: 99%
“…HO-1 effect is complex due to the multiple products of its activity, the non-canonical actions of the protein and the plethora of interactions of the products and protein with other pathways [141]. [90] and Ahmad et al [64].…”
Section: Remaining Questionsmentioning
confidence: 99%
“…Taking into account the involvement of HO-1 in PCa demonstrated by us and other authors [11,16,42,43], we were keen to identify HO-1 molecular partners responsible for the biological effects provoked by HO-1 induction in prostate tumorigenesis. The literature reflects controversial results regarding the role of HO-1 in carcinogenesis [7]. Some evidence suggests that HO-1 can act as a protective enzyme, decreasing the risk of developing certain tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Conclusions: ANXA2/HO-1 rises as a critical axis in PCa.Biomolecules 2020, 10, 467 2 of 24 microenvironment communicate and interact with each other to develop a fertile niche for the promotion of the metastatic process [3][4][5].Evidence has recognized inflammation as a risk factor for this neoplastic disease [6]. Heme oxygenase 1 (HO-1), encoded by the HMOX1 gene, is a stress response protein and a critical mediator of cellular homeostasis [7]. Although the role of HO-1 in cancer is controversial [8,9], we have shown that its pharmacologic or genetic upregulation is associated with a less aggressive phenotype in PCa [10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6 HO-1 is also implicated in the modulation of cellular adhesion in PCa, upregulating E-cadherin and β -catenin expression, and relocating them to the cell membrane, 7 favoring a more epithelial phenotype. However, it is yet unclear which are the HO-1 interactors and how they cooperate in the regulation of the cytoskeleton organization.…”
mentioning
confidence: 99%